Work-Life Balance Analysis of Employees at PILAR PKBI Central Java Province - Putri Ayu Anita; Khairani Zikrinawati; Lucky A de Sessiani (Health Science Udinus, 2025)
Work-life balance (WLB) has become one of the key issues in today’s working environment, including among employees of non-profit organizations such as the Indonesian Family Planning Association (PKBI) of Central Java Province. WLB refers to a condition in which individuals can allocate their time and energy evenly between work and personal life, which in turn can improve quality of life, mental well-being, and productivity. However, achieving WLB is not easy and is influenced by various factors. This study uses a descriptive qualitative approach. Data were collected through in-depth interviews using open-ended questions to explore the informants’ views and experiences regarding work-life balance. Based on interviews with employees at PKBI, it can be concluded that maintaining a balance between work and personal life is a top priority for them. However, efforts to achieve this balance are affected by the unpredictable nature of their work, which often requires a high degree of flexibility in managing time and tasks.